2016
DOI: 10.1128/msphere.00082-16
|View full text |Cite
|
Sign up to set email alerts
|

The Response Regulator BfmR Is a Potential Drug Target for Acinetobacter baumannii

Abstract: Increasing antibiotic resistance in bacteria, particularly Gram-negative bacilli, has significantly affected the ability of physicians to treat infections, with resultant increased morbidity, mortality, and health care costs. In fact, some strains of bacteria are resistant to all available antibiotics, such as Acinetobacter baumannii, which is the focus of this report. Therefore, the development of new antibiotics active against these resistant strains is urgently needed. In this study, BfmR is further validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 71 publications
4
87
0
Order By: Relevance
“…A study made by Russo et al . () revealed that the bfmR mutant decreased the A. baumannii survival in human serum. In addition, BfmR controls EPS production, pilus assembly system, cell attachment and biofilm formation (Thompson et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A study made by Russo et al . () revealed that the bfmR mutant decreased the A. baumannii survival in human serum. In addition, BfmR controls EPS production, pilus assembly system, cell attachment and biofilm formation (Thompson et al .…”
Section: Discussionmentioning
confidence: 98%
“…BfmR is the response regulator of a two-component signal transduction system, which transmits the signal from the sensor histidine kinase (BfmS) and acts as a transcriptional regulator. A study made by Russo et al (2016) revealed that the bfmR mutant decreased the A. baumannii survival in human serum. In addition, BfmR controls EPS production, pilus assembly system, cell attachment and biofilm formation (Thompson et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the genes identified as essential in vivo overlapped poorly with genes that were previously identified as essential in other Gram negative species under laboratory conditions, and none of them are targeted by clinically used antibiotics or antimicrobial molecules that are currently being developed. In a later study, the same authors validated one of the essential genes identified in this study, the gene encoding the response regulator BfmR, as a potential target for the development of novel antibiotics [51]. …”
Section: Essential Genes As Targets For Antibiotic Discoverymentioning
confidence: 99%
“…It is also known that genes encoding Bap protein and efflux pumps are important for biofilms (Brossard and Campagnari, 2012;He et al, 2015;Loehfelm et al, 2008;Tomaras et al, 2008Tomaras et al, , 2003. The BfmR response regulator is part of a two-component system (BfmRS) (Farrow et al, 2018;Geisinger and Isberg, 2015;Russo et al, 2016;Tomaras et al, 2008;Wang et al, 2014) that results in BfmR phosphorylation. It is unknown if bfmR expression is induced by another factor or whether de-repression by phosphorylated BfmR, with lower affinity for its operator site (Draughn et al, 2018), is enough for induction.…”
Section: Introductionmentioning
confidence: 99%